2007
DOI: 10.1007/s10549-007-9587-7
|View full text |Cite
|
Sign up to set email alerts
|

Cancer-specific targeting of a conditionally replicative adenovirus using mRNA translational control

Abstract: Background-In view of the limited success of available treatment modalities for a wide array of cancer, alternative and complementary therapeutic strategies need to be developed. Virotherapy employing conditionally replicative adenoviruses (CRAds) represents a promising targeted intervention relevant to a wide array of neoplastic diseases. Critical to the realization of an acceptable therapeutic index using virotherapy in clinical trials is the achievement of oncolytic replication in tumor cells, while avoidin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 41 publications
0
18
0
Order By: Relevance
“…For example, Rodriguez et al inserted a prostate-specific antigen gene enhancer element upstream of the E1A gene to restrict viral replication to prostate cancer cells (40). Recently, regulatory elements from prostaglandin-endoperoxide synthase-2 (2) and fibroblast growth factor-2 (43) have been employed to favor the stability and translation, respectively, of E1A mRNA in certain types of cancer cells.…”
mentioning
confidence: 99%
“…For example, Rodriguez et al inserted a prostate-specific antigen gene enhancer element upstream of the E1A gene to restrict viral replication to prostate cancer cells (40). Recently, regulatory elements from prostaglandin-endoperoxide synthase-2 (2) and fibroblast growth factor-2 (43) have been employed to favor the stability and translation, respectively, of E1A mRNA in certain types of cancer cells.…”
mentioning
confidence: 99%
“…For example, virotherapy with conditionally replicating adenoviruses (CRAds) has been shown to be a promising intervention relevant to a wide array of neoplastic diseases (Stoff-Khalili et al, 2008). Adenoviruses have many advantages, including their ability to infect a wide variety of cells, their easy replication, and their relative safety.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is consistent with other work demonstrating the ability to target cancer cells using FGF-2 deived 5 0 UTR in adenovirus system. 28 Prostate-specific PTEN À/À mice are transgenic models that develop prostate cancer with disease progression, which mimic that seen in patients. Several studies have demonstrated that deletion and/or mutation of the PTEN gene leads to upregulation of the AKT/mTOR pathway, which can lead to increased eIF4E expression.…”
Section: Discussionmentioning
confidence: 99%